PELABELAN CORDIAL UNTUK GRAF SPLIT DARI BEBERAPA GRAF - Nisa Erma Fitriana; Lucia Ratnasari (Jurnal Matematika, 2012)
Cordial labeling is a binary point labeling that have absolute value condition of the difference in the number of vertices having label 0 and the number of vertices having label 1 is less than or equal to 1 dan absolute value of the difference in  the number of edges having label 0 and the number of edges having label 1 is less than or equal to 1. Graph which qualified of cordial labeling is called cordial graph. Split graph S(G) is the graph obtained by taking a new vertex v’ for each vertex v of a graph G , a new vertex v’ is connected to all vertices of G which adjacent to v . In this final paper explored about cordial labeling for split graph of path graph, cycle graph, wheel graph, matching graph, fan graph, bipartite complete graph, and k copies star graph